2006
DOI: 10.1002/ijc.21968
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genes upregulated by the demethylating agent 5‐aza‐2′‐deoxycytidine in gastric cancer cell lines

Abstract: In gastric cancer, increasing numbers of genes have been reported to be silenced by aberrant methylation. However, global analysis of epigenetic inactivation in cancer cells has rarely been performed. For screening the genes upregulated by the demethylating agent 5-aza-2 0 -deoxycytidine (DAC), cDNA microarray analysis (AceGene 1 , containing 30,000 genes) was performed using gastric cancer cell lines (AGS, MKN74, MKN1, MKN45 and Kato3) treated with DAC. The candidate upregulated genes were confirmed by real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
1
29
1
Order By: Relevance
“…The cell membrane is thus depleted of LRP receptors, and Wnt signaling is inhibited to a greater extent and for longer (27). Previous studies have shown that the expression of Dkk1 is downregulated in human colon cancer, gastric cancer and melanoma tissues, indicating that Dkk1 may act as a tumor suppressor in these types of cancer and not as an antagonist of Wnt signaling (13,14,28,29). However, Dkk1 has been found to be overexpressed in hepatoblastoma and hepatocellular carcinoma, indicating that Dkk1 may be regulated by a feedback loop activated by the Wnt signaling pathway.…”
Section: A B C Dmentioning
confidence: 99%
“…The cell membrane is thus depleted of LRP receptors, and Wnt signaling is inhibited to a greater extent and for longer (27). Previous studies have shown that the expression of Dkk1 is downregulated in human colon cancer, gastric cancer and melanoma tissues, indicating that Dkk1 may act as a tumor suppressor in these types of cancer and not as an antagonist of Wnt signaling (13,14,28,29). However, Dkk1 has been found to be overexpressed in hepatoblastoma and hepatocellular carcinoma, indicating that Dkk1 may be regulated by a feedback loop activated by the Wnt signaling pathway.…”
Section: A B C Dmentioning
confidence: 99%
“…In colon cancer, Gonzalez-Sancho et al (2005) reported that the loss of DKK1 expression may open the door to cancer by removing the inhibitory effect on the Wnt/b-catenin pathway. Dickkopf-1 epigenetic inactivation may be a consequence of CpG methylation (Aguilera et al, 2006;Mikata et al, 2006). However, hypermethylation has been observed in only 17% of colon cancer clinical specimens, which indicates that this phenomenon is real but cannot be generalised (Aguilera et al, 2006).…”
Section: A B C E Dmentioning
confidence: 99%
“…In our previous study using cDNA microarray and real-time PCR, five genes were identified to be up-regulated by DAC treatment in gastric cancer cell lines (7). Of these, BCL2L10 was hypermethylated in 4 of 5 gastric cancer cell lines, and its CpG island became demethylated with the restoration of its expression after DAC treatment.…”
Section: Discussionmentioning
confidence: 98%
“…We previously analyzed the genes induced by the demethylating agent 5-aza-2'-deoxycytidine (DAC) in gastric cancer cell lines using a cDNA microarray containing 30,000 genes. We found that BCL2L10, which belongs to the proapoptotic Bcl-2 family, was transcriptionally repressed by promoter hypermethylation (7). BCL2L10 (also called Diva) has been reported to directly interact with Apaf-1 and to displace Bcl-X L , suggesting it inhibits Bcl-X L function and promotes apoptosis (8).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation